Asia Pacific in the age of globalization - Johnson, Robert David 1967- (The Palgrave Macmillan transnational history series, 2015)
"Asia Pacific in the Age of Globalization examines United States-East Asian relations in the framework of global history, incorporating fresh insights that have been offered by scholars on such topics as globalization, human rights, historical memory, and trans-cultural relations. It brings the history of trans-Pacific relations up to date, both chronologically and conceptually. As the wider Pacific is destined to play an increasingly crucial role in the world's strategic, political, economic, and cultural affairs, this volume will be of invaluable help to readers seeking to understand such a development in a global historical framework"..